TRANFORMASI NILAI-NILAI PERUSAHAAN KEPADA KARYAWAN - Nazwirman Nazwirman (Universitas Bina Sarana Informatika, 2012)
The company's value to include values play, aspirational, Accidental Core values and the culture of the company's core values that drive the actions of employees. Corporate culture is integrity, how to align shared common values and employee behavior. In force in the workplace, corporate culture must be collaborative, culturally and creatively. Corporate culture must be tranformation employees' lives and empower employees to change the lives of others. The integrity building, the company can compete in the labor market talent, increase productivity and meeting with customers, and manage differences. Market value to employees is as important as the mission to the consumer market. This paper uses explanatory methods, namely dig as much information from various sources of information, the goal is to provide information and an overview of the company's values to employees.Keywords: corporate values, employees